Theology and Economics - Kidwell, Jeremy. author. aut Link
IX, 293 p.
Keywords: This volume brings together a prominent group of Christian economists and theologians to provide an interdisciplinary look at how we might use the tools of economic and theological reasoning to cultivate more just and moral economies for the 21st century.